Animal rights and animal laws in the Bible the daily practice of reverence for life - Vasantha Rao, Chilkuri (Lewiston : The Edwin Mellen Press, 2011)
What characterizes the proper ethical treatment of animals as outlined in the Old Testament? Animals play an important role in the Old Testament, and in particular the Pentateuch. Ritual sacrifices were a part of the ancient traditions, and there are rules written into the laws that pertain to this practice as well as the religious approach to animals and nature. In the oft quoted passage from Genesis the call is to not only be fruitful and multiply, but to reign over the earth and subdue it along with the animals that God created. The author explores the fallout of an anthropocentric way of a.
ANIMAL RIGHTS AND ANIMAL LAWS IN THE BIBLE: The Daily Practice of Reverence for Life; Copyright Page; Dedication; Table of Contents; Acknowledgments; Foreword; Chapter-One; Chapter-Two; Chapter-Three; Abbreviations; Bibliography
Description based upon print version of record.
Includes bibliographical references.
Keywords: Animal welfare -- Biblical teaching; Animal welfare (Jewish law).; Bible. O.T. Pentateuch -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc; Animal welfare -- Biblical teaching; Animal welfare (Jewish law); RELIGION / Biblical Studies / Old Testament; Electronic books; Electronic books